Root Resorptıon Durıng Bıcuspıd Intrusıon Wıth Varyıng Force Magnıtudes - Nazan Küçükkeleş; Ahu Acar; İmer Okar (Galenos Yayinevi, 1996)
This study was carried out on 14 upper first premolars the extractions of which were planned as a part of orthodontic treatment. Of 14 teeth, 10 formed the test group and 4, the control group. Three of the test teeth were intruded with a continuous force of 50 g, the other three, with a force of 100 g, and the remaining four, with a force of 150 g. No force was applied on the teeth which served as controls. The experimental period was two months. Informed consents of the subjects were taken prior to the onset of the study. At the end of two months, all teeth were extracted and prepared for examination on a scanning electron microscope. Apical root resorption was observed with all three force values. While the diameters of the resorption lacunes in the 50 g group were approximately 30-40 microns, the resorption lacunes tented to grow as wide as 200-300 microns as the force values increased. While the resorption was limited to cementum with light force, dentin was involved as force magnitude increased. Resorption lacunae had typical elliptical shapes with their long axis lying in apical-coronal direction. The ones near the coronal regions of the root surface tented to get wider but more shallow.